Bacteriocin Activity of Lactic Acid Bacteria Isolated from Rumen Fluid of Thin Tail Sheep - Okti Widayati; Zaenal Bachruddin; Chusnul Hanim; Lies Mira Yusiati; Nafiatul Umami (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
The objective of this study was to determine the activity and the stability of bacteriocin from lactic acid bacteria (BAL) isolated from rumen fluid of thin-tail sheep under the temperature (80, 100, and 121°C), pH (3, 7, and 10), and the length of storage (for 2 weeks under the temperature -8, 11, and 29°C). Lactic acid bacteria obtained by isolation, selection, and identification of thin-tailed sheep rumen fluid were used for bacteriocin production. The crude bacteriocin was partially purified using 70% ammonium sulfate, then was dialysis for 12 hours. The obtained bacteriocin then tested its inhibitory activity against E.coli (representing Gram-negative) and S. aureus (representing Gram-positive) under temperature (80, 100, and 121°C), pH (3, 7, and 10), and the length of storage (for 2 weeks under the temperature -8, 11, and 29°C). The data of bacteriocin activity based on pH, temperature, and the length of storage were analyzed with factorial, then when there was a significant difference of variable because treatment was continued with Duncan's Multiple Range Test (DMRT) test. The results showed that the bacteriocin activity of the three types of BAL against S.aureus is greater than E.coli. The highest activity was shown in pH 3, while the lowest activity was shown at pH 10 (P<0.01). The highest activity was shown at a heating temperature of 100°C, while the lowest activity was shown at a heating temperature of 80°C (P<0.01). The activity of bacteriocin produced by BAL 0 A, BAL 1 A, and BAL 4 C tended to be stable to the heating temperature of 80, 100, and 121°C but decreased with increasing pH value (pH 3, 7, and 10). The best of bacteriocin activity was found at pH 3 (acid), heating at 100°C, and stored at -8°C for 14 days.